Multilingualism in Post-Soviet Countries. - Pavlenko, Aneta (Multilingual Matters, 2008)
Post-Soviet countries have emerged as a contested linguistic space, where disagreements over language and education policies have led to demonstrations, military conflicts and even secession. This collection offers a comparative analysis of language and education policies and practices in post-Soviet countries.